Views of general practitioners and pharmacists on the role of the pharmacist in HIV/Aids management - E. van der Walt; R.S. Summers (South African Family Practice)
Background: Sub-Saharan Africa is home to 25.8 million people living with HIV/Aids. In November 2003, the South African government approved The Operational Plan for Comprehensive Treatment and Care for HIV and Aids, which aimed to provide antiretroviral treatment to 500 000 patients by the end of 2007. The successful implementation of this operational plan requires many healthcare providers trained in aspects of HIV. This study aimed to establish and compare the views of general practitioners and pharmacists on the role of the pharmacist in HIV/Aids management and to elucidate an appropriate role for pharmacists. Ethical approval was obtained from the MEDUNSA Research Ethics and Publications Committee.